Litiasis biliar o colecistectomía asociada a síndrome metabólico en pacientes del Hospital II - EsSalud, Huánuco - Fierro Barzola, William (2018)
Introduction: The objective of the present study was to determine that a relationship exists between gallstones or cholecystectomy in patients with metabolic syndrome Hospital II - Essalud, Huanuco 2014. Methods: A study of cases and controls was performed on a case-A crosssectional study was conducted on 360 subjects (213 men and 147 women) all insured patients EsSalud and were evaluated to be part of program "Reform of life" in the same institution. 180 people with metabolic syndrome (cases) and 180 who did not have metabolic syndrome (controls) were included; is excluded people under 18 and people with psychiatric illness. A survey that asked people their age, gender, type of diet, family medical history, metabolic syndrome and cholecystectomy was performed. Results: Of the 360 subjects, compared to cholecystectomy, it was found that 162 (51.3%) were not cholecystectomy and did not have metabolic syndrome; 154 (48.7%) had metabolic syndrome cholecystectomy yes, that is a significant relationship (p = 0.198) was found, but quality can be attributed risk for metabolicsyndrome (OR = 1.519, CI = 0801-2882). As for gallstones, those who did not present calculations 171 (50.4%) had metabolic syndrome and 168 (49.6%) had metabolic syndrome itself, but which had bile, 9 (42.9%) did make calculations metabolic syndrome and 12 (57.1%), then no significant relationship (p = 0.5 was found, however, gallstones itself constitutes a risk factor. the male gender was the highest estimated incidence of metabolic syndrome, these were 111 (52.1%), on the other hand, were over 35 139 (47.1% of them) those with metabolic syndrome. When considering diet significantly (p = 0) is, but depending on the level of consumption fat. Conclusions: There is no significant relationship between cholecystectomy or gallstones with the metabolic syndrome.